Essentials of mineral exploration and evaluation - Gandhi, S. M.; Sarkar, B. C. (Amsterdam, Netherlands : Elsevier, 2016)
Essentials of Mineral Exploration and Evaluation offers a thorough overview of methods used in mineral exploration campaigns, evaluation, reporting and economic assessment processes. Fully illustrated to cover the state-of-the-art exploration techniques and evaluation of mineral assets being practiced globally, this up-to-date reference offers balanced coverage of the latest knowledge and current global trends in successful mineral exploration and evaluation. From mineral deposits, to remote sensing, to sampling and analysis, Essentials of Mineral Exploration and Evaluation offers an extensive look at this rapidly changing field. Covers the complete spectrum of all aspects of ore deposits and mining them, providing a "one-stop shop" for experts and students Presents the most up-to-date information on developments and methods in all areas of mineral exploration Includes chapters on application of GIS, statistics, and geostatistics in mineral exploration and evaluation Includes case studies to enhance practical application of concepts.
Metals and minerals : global trends, outlook, and mineral exploration -- Mineral deposits : types and associations -- Reconnaissance and prospecting -- Remote sensing techniques -- Geophysical exploration -- Geochemical exploration -- Geological exploration -- Drilling -- Sampling and analysis -- Geographic information system and common earth model -- Conventional and statistical resource/reserve estimation -- Geostatistical resource/reserve estimation -- Mineral resources classification -- Valuation of mineral properties.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed May 19, 2016).
Includes bibliographical references and index.
Keywords: Prospecting; Mine valuation; Mines and mineral resources; TECHNOLOGY & ENGINEERING / Mining; Mine valuation; Mines and mineral resources; Prospecting; Electronic books; Electronic book